Root canal anatomy and morphology of permanent maxillary Lateral Incisors in an Iranian population - Kuzekanani, Maryam; Parvazeh, Saadollah (Italian Journal of Anatomy and Embryology, 2022)
A meticulous knowledge of the root canal anatomy and morphology of the teeth is imperative to achieve successful root canal and also many other dental and surgical treatments on them. The purpose of this study was to study the root canal anatomy and morphology of permanent maxillary Lateral incisors in Kerman. 100 extracted intact permanent maxillary Lateral incisor teeth were collected from different dental clinics in Kerman. The anatomic and morphologic characteristics of the selected samples such as the number of roots, the apical root curve direction and the length of the teeth were determined by macroscopic evaluation and length assessment of each sample. After staining, decalcification and clearing of each tooth the existence and location of additional and lateral canals was also carefully explored by using magnifying tools. All maxillary Lateral incisors had just one root and one root canal and the average length for this tooth was 22.5 mms in this study. The curvature of the roots in 67% of the samples was distally, in 5%; bucally, in 2%; palatally and in 3%; mesially. 23% of the teeth had straight roots and root canals. Also, 29% of the teeth had lateral canals that in 89% of the cases were located in the apical thirds, in 11%; in the middle and in none of the cases in the coronal thirds. As a conclusion lateral canals and curved apex which are thorough challenges in dentistry are prevalent in maxillary lateral incisors among this south eastern Iranian population.